Implementation of Human Values to Create Prosperity in Society - Siti Ronisah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Human Values consist of truth, virtue, peace, compassion and non-violence, which are values that are relevant to the values of national character in everyday reality, every human being, group and society is always required to behave and behave based on basic values (cultural values) which are views of life or life guidelines that are selected selectively from existing values. The values that exist in humans are usually acquired from earliest childhood and are imbued with extraordinary social and cultural connotations, since they depend greatly on the context in which a person lives. Human and social values must be applied in the daily lives of people who live in society with the aim of making life much more peaceful and also safe from threats or similar bad things that can damage social life.